Development of a business model resilience framework for managers and strategic decision-makers - Marija Radic; P. Herrmann; P. Haberland; Carla R. Riese (Schmalenbach Journal of Business Research (SBUR), 2022)
Following the massive impact of the Covid-19 pandemic on the global economy and on small and medium-sized enterprises (SMEs) in particular, the concept of resilience has experienced a renaissance. As an organizational concept, business model resilience describes the extent to which an organization can maintain or quickly recover its value proposition despite unexpected current or future disruptions (Palzkill-Vorbeck 2018). Although research has been conducted in this area for decades, there is still a lack of a unified framework that brings together the findings from research and links them to organizational practice. The paper addresses this gap by developing a framework for business model resilience and demonstrating its practical relevance for organizational performance during the Covid-19 pandemic in 2020. The framework includes 11 factors that characterize the resilience of an organization's business model. For managers and decision-makers, the framework is an opportunity to assess and improve the resilience of their organizations. For researchers, the framework is an important foundation for transferring the concept of business model resilience into organizational practice.
Keywords: D22; D24; E32; H12; L14; L23; L25; M11; M12; M51; 650; Resilience; Framework; Business model; Business model resilience; Covid-19; SME